2004
DOI: 10.1111/j.0022-3506.2004.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

High Self‐Control Predicts Good Adjustment, Less Pathology, Better Grades, and Interpersonal Success

Abstract: What good is self-control? We incorporated a new measure of individual differences in self-control into two large investigations of a broad spectrum of behaviors. The new scale showed good internal consistency and retest reliability. Higher scores on self-control correlated with a higher grade point average, better adjustment (fewer reports of psychopathology, higher self-esteem), less binge eating and alcohol abuse, better relationships and interpersonal skills, secure attachment, and more optimal emotional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

136
4,489
11
232

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 5,043 publications
(4,868 citation statements)
references
References 111 publications
136
4,489
11
232
Order By: Relevance
“…The study confirmed that insufficient self-control is a predictor of Facebook addiction. This is in accordance with the general trend presented in the subject literature, stressing that people with good self-control cope better in life, can hold their temper, do not abuse alcohol, keep secrets, and save money [9]. Also, some findings indicate that people with a high level of self-control can use the Internet in a healthy way [11].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The study confirmed that insufficient self-control is a predictor of Facebook addiction. This is in accordance with the general trend presented in the subject literature, stressing that people with good self-control cope better in life, can hold their temper, do not abuse alcohol, keep secrets, and save money [9]. Also, some findings indicate that people with a high level of self-control can use the Internet in a healthy way [11].…”
Section: Discussionsupporting
confidence: 89%
“…The Brief Self-Control Scale [9] was used to measure dispositional self-control. It consists of 13 items (e.g., I am good at resisting temptation).…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…We excluded seven items as they either loaded on the wrong factor (Q7 from the surface factor), had significant cross loadings (Q4 from the strategic factor and Q8, 9, 17, and 20 from the surface factor), or had no loadings above .3 (Q18 from the deep factor) (for items, see Brief self-control scale (BSCS). The Self-control scale is developed by Tangney, Baumeister, and Boone (2004). We used the brief version including 13 items (e.g.…”
Section: To What Degree Do You Feel That You Have Learned Useful Studmentioning
confidence: 99%